Phytochemical-rich medicinal plant extracts suppress bacterial antigens-induced inflammation in human tonsil epithelial cells - Wijesundara, Niluni M. (PeerJ, 2017)
BACKGROUND: Pharyngitis is an inflammatory condition of the pharynx and associated structures commonly caused by the Group A streptococci (GAS). There is a growing interest in discovering plant-based anti-inflammatory compounds as potential alternatives to conventional drugs. This study evaluated anti-inflammatory activity of phytochemical-rich extracts prepared from 12 herbal plants using human tonsil epithelial cells (HTonEpiC) in vitro. METHODS: The HTonEpiC were induced by a mixture of lipoteichoic acid (LTA) and peptidoglycan (PGN) (10 µg/mL; bacterial antigens) for 4 h and then exposed to ethanol extracts (EE) or aqueous extracts (AE) for 20 h. The secretion of four pro-inflammatory cytokines was measured using enzyme-linked immunosorbent assays (ELISA). Total phenolic and total flavonoid contents of the extracts were determined using spectrophotometric methods. RESULTS: The herbal plant extracts (≤5 µg/mL) were not cytotoxic to HTonEpiC. The extracts exhibited a broad range of reduction (1.2%–92.6%) of secretion of interleukin-8 (IL-8), human beta defensin-2 (hBD-2), epithelial-derived neutrophil activating protein-78 (ENA-78), and granulocyte chemotactic protein-2 (GCP-2). Both EE and AE of clove, ginger, and echinacea flower and EE from danshen root significantly inhibited the pro-inflammatory cytokine production as induced by LTA and PGN in HTonEpiCs at the concentrations of 1 and 5 µg/mL. DISCUSSION: Our observations indicate that danshen root, clove, ginger, and echinacea flower extracts exhibit an anti-inflammatory effect in HTonEpiCs. The most efficacious extracts from danshen root, clove, ginger and echinacea flowers have potential to be used as natural sources for developing phytotherapeutic products in the management of painful inflammation due to streptococcal pharyngitis.